2015
DOI: 10.3923/ajcs.2015.233.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungi on Growth and Development of Potato (Solanum tuberosum) Plant

Abstract: Arbuscular Mycorrhizal Fungi (AMF) have mutualistic relationships with more than 80% of terrestrial plant species. Arbuscular mycorrhizal fungal symbiosis have remarkable role in sustainable growth and development of plants as they help the land plants to acclimatize the biotic and abiotic conditions for their better survival, growth and development. In the present study surface sterilized tubers and seeds of potato were sown in earthen pots filled with sterile soil. Half the pots were inoculated with steriliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The results of large scale field trials indicated that inoculation of potato with R. irregularis DAOM 197198 caused significant increase in tuber yield, and the effect was cultivar independent (Hijri, 2016). The positive effect of R. intraradices and F. mosseae on the host morphological parameters was found for two potato cultivars (Jyoti and TPS) (Lone et al, 2015). Root colonization with AMF improved fresh and dry matter of both plant shoot and root, increased the chlorophyll content and tuber yield.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of large scale field trials indicated that inoculation of potato with R. irregularis DAOM 197198 caused significant increase in tuber yield, and the effect was cultivar independent (Hijri, 2016). The positive effect of R. intraradices and F. mosseae on the host morphological parameters was found for two potato cultivars (Jyoti and TPS) (Lone et al, 2015). Root colonization with AMF improved fresh and dry matter of both plant shoot and root, increased the chlorophyll content and tuber yield.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous experiments conducted under greenhouse, shade house and field conditions showed that potato roots are prone to establish endomycorrhiza with several AMF species, including Rhizophagus intraradices (formerly Glomus intraradices), Rhizophagus irregularis (formerly Glomus irregulare), Funneliformis mosseae (formerly Glomus mosseae), or Gigaspora sp. (Douds et al, 2007;Gallou et al, 2011;Lone et al, 2015;Hijri, 2016). Mycorrhizal potato plants were reported to display improved growth, pathogen resistance, and productivity compared to non-mycorrhizal ones (Douds et al, 2007;Bharadwaj et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in Fig.1 confirms that all the treatments, where bio fertilizers were applied, showed significant improvement in emergence and survival of plants. The plants of T (50% of RDF + PSB+ Azotobacter+ VAM+ Mustard 8 cake) took least (18.33) number of days for complete emergence with highest (98.44%) survival, followed by T (20 days and 6 97.91%, respectively) and T (20 days and 97.13%) which might 5 be due to increased availability of bio-stimulants or growth promoting substances like phytohormones and vitamins in the presence of Azotobacter (Bhattacharya et al, 2000, Kumar et al, 2001. Lone et al (2015 had also confirmed better emergence of potato plants under application of biofertilizers .…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular Mycorrhizal Fungi (AMF) are the largely prevalent type of ecologically vital root fungal symbionts in higher plant species, being essential for sustainable growth and development and the survival of several land plants (Lone et al, 2015). The AMF are very important for improvement of soil quality through their beneficial effects on host plant physiology and for the soil ecology interactions, thus improving soil structure and stability (Hallett et al, 2009;Husna et al, 2015).…”
Section: Introductionmentioning
confidence: 99%